POTENSI SAGU (METROXYLON SP.) DALAM MENDUKUNG KETAHANAN PANGAN DI PROVINSI RIAU - Syartiwidya Syartiwidya (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2023)
Riau Province has a large potential for sago (Metroxylon sp). This is indicated by an area of ​​84,780 hectares and a production of 260,658 tons/year (Riau Plantation Office, 2020). The use of sago starch is still limited as a staple food for certain communities. Sago with a high nutritional content of carbohydrates equivalent to rice is an all-around plant, which means a plant that has many benefits. Besides sago can reducing dependence on imported flour, rice imports are also used as food ingredients that are processed into various forms of processed food, as well as non-food ingredients. such as renewable energy sources, namely bioethanol and pharmaceutical industry materials. Sago waste also provides many benefits, such as bark as flooring for houses, roads, and firewood, midrib as roofs, and pith pulp as animal feed, adhesives, charcoal briquettes, board particles, and composting materials. Optimizing the utilization of sago potential if it can be applied through food diversification efforts will open up economic activities and support food security in Riau Province. Provinsi Riau memiliki potensi sagu (Metroxylon sp) yang cukup besar. Hal ini ditunjukkan oleh luas area seluas 84.780 Ha dan produksi sebesar 260.658 ton/tahun (Dinas Perkebunan Provinsi Riau, 2020). Pemanfaatan pati sagu masih terbatas sebagai pangan pokok masyarakat tertentu. Sagu dengan kandungan gizi tinggi karbohidrat setara beras tersebut merupakan tumbuhan serba gatra yang artinya tumbuhan yang mempunyai banyak manfaat. Selain sagu dapat mengurangi ketergantungan terhadap impor terigu, impor beras juga sebagai bahan pangan yang diolah menjadi berbagai bentuk olahan pangan, serta juga sebagai bahan non pangan seperti sumber energi terbarukan, yaitu bioetanol dan bahan industri farmasi. Limbah sagu juga memberikan banyak manfaat, seperti kulit batang sebagai lantai rumah, jalan dan kayu bakar, pelepah sebagai atap rumah, dan ampas empulur sebagai pakan ternak, bahan perekat, brikat arang, papan partikel dan bahan pembuat kompos. Optimalisasi potensi sagu ini bila dapat diterapkan melalui upaya penganekaragaman pangan yang akan membuka kegiatan ekonomi dan mendukung ketahanan pangan di Provinsi Riau.